PENGARUH EKSTRAK UMBI BAWANG DAYAK (Eleutherine americana Merr.) TERHADAP PENURUNAN TRIGLISERIDA DARAH TIKUS JANTAN WISTAR DAN POTENSINYA SEBAGAI RANCANGAN MODUL BIOLOGI KELAS XI SMA - Jannah, Nurul; Yustina, Yustina; Wulandari, Sri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : Hypertriglyceride is a condition characterized by a triglyceride level above the normal threshold. High triglyceride levels cause disruption to the circulatory system. This study aims to determine the effect of Dayak bulb extract (Eleutherine americana Merr.) On the decrease of blood triglyceride in white male rats Wistar strain. This research is included in the correct experiment with the Post Only Control Group Design design. The results showed that the negative control group (K1) had the highest triglyceride levels with the other group (119.75 ± 21.36 mg / dL); the positive control group (K0) with triglyceride levels (104.33 ± 5.68 mg / dL) was higher than the dayak dose group 100 mg / KgBB (P1) and day dose of 200 mg / KgBB P2 . The P2 group had a triglyceride level of (58.5 ± 13.32 mg / dL) lower than the P1 group (64 ± 27.14 mg / dL). The results of statistical tests with Anova one way showed that there were significant differences between treatment groups (p = 0,002). It was concluded that administration of Dayak bulb extract had an effect on the decrease of blood triglyceride in Wistar white male rats.Key Words: Hypercholesterolemia; Onion Dayak (Eleutherine americana Merr.); Triglycerids;and Wistar rats